Measurement of the Z(→ l+l-)γ production cross-section in pp collisions at √s=13 TeV with the ATLAS detector - Aad, Georges; Anders, Christoph; Andrei, George Victor; Antel, Claire; Bolz, Arthur; Dunford, Monica; Ferreira de Lima, Danilo Enoque; Franchino, Silvia; Geisler, Manuel Patrice; Helary, Louis; Henkelmann, Lars; Jongmanns, Jan; et al. (Journal of high energy physics, 2020)
The production of a prompt photon in association with a Z boson is studied in proton-proton collisions at a centre-of-mass energy s = 13 TeV. The analysis uses a data sample with an integrated luminosity of 139 fb(-1) collected by the ATLAS detector at the LHC from 2015 to 2018. The production cross-section for the process pp -> l(+)l(-)gamma + X (l = e, mu) is measured within a fiducial phase-space region defined by kinematic requirements on the photon and the leptons, and by isolation requirements on the photon. An experimental precision of 2.9% is achieved for the fiducial cross-section. Differential cross-sections are measured as a function of each of six kinematic variables characterising the l(+)l(-)gamma system. The data are compared with theoretical predictions based on next-to-leading-order and next-to-next-to-leading-order perturbative QCD calculations. The impact of next-to-leading-order electroweak corrections is also considered.
Das Plus- und Minuszeichen in l+l- im Titel ist hochgestellt, das s steht unter dem Wurzelzeichen
The ATLAS Collaboration: G. Aad, V. C.F. Anders, V. Andrei, C.Antel, A.C. Bolz, M. Dunford, D.E. Ferreira de Lima, S. Franchino, M.P. Geisler, L. Helary, J. Jongmanns, M. Klassen, M. Kolb, A. Krishnan, A. Kugel, M. Lisovyi, H. Meyer zu Theenhausen, F. Napolitano, P.S. Ott, M. Sahinsoy, A. Schoening, H.-C. Schultz-Coulon, T.M. Spieker, R. Stamen, P. Starovoitov, S. Suchek, L. Vigani, J. Wang, S.M. Weber, M. Wessels, X. Yue und 2923 weitere
Gesehen am 17.04.2020